O wartościowaniu dóbr ekonomicznych - Giza, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2015)
The presented study includes an analysis of the category of ‘good’ on the basis ofphilosophy and economics. Particular attention was paid here to the factors determiningthe monetary value (price) of an economic good. While achieving the assumedobjective of the research, answers to the following questions were sought:What is the difference, therefore, in the interpretation of good as an axiomatic categoryand good which the economy deals with? What is the basis for the valuationof goods which are the subject of economic analysis? While seeking answers tothese questions, an attempt was made to justify the thesis according to which contemporaryunderstanding of the way of valuating goods by the market is limited toaccepting the price understood as a variable representing a kind of relationship setin a given time period.